Response to M. tuberculosis selected RD1 peptides in Ugandan HIV-infected patients with smear positive pulmonary tuberculosis: a pilot study - Girardi Enrico; Mugerwa Michael; Baseke Joy; Mayanja-Kizza Harriet; Carrara Stefania; Goletti Delia; Toossi Zahra (BMC Infectious Diseases, 2008)
Abstract Background Tuberculosis (TB) is the most frequent co-infection in HIV-infected individuals still presenting diagnostic difficulties particularly in developing countries. Recently an assay based on IFN-gamma response to M. tuberculosis RD1 peptides selected by computational analysis was developed whose presence is detected during active TB disease. Objective of this study was to investigate the response to selected RD1 peptides in HIV-1-infected subjects with or without active TB in a country endemic for TB and to evaluate the change of this response over time. Methods 30 HIV-infected individuals were prospectively enrolled, 20 with active TB and 10 without. Among those with TB, 12 were followed over time. IFN-gamma response to selected RD1 peptides was evaluated by enzyme-linked immunospot (ELISPOT) assay. As control, response to RD1 proteins was included. Results were correlated with immune, microbiological and virological data. Results Among patients with active TB, 2/20 were excluded from the analysis, one due to cell artifacts and the other to unresponsiveness to M. tuberculosis antigens. Among those analyzable, response to selected RD1 peptides evaluated as spot-forming cells was significantly higher in subjects with active TB compared to those without (p = 0.02). Among the 12 TB patients studied over time a significant decrease (p =< 0.007) of IFN-gamma response was found at completion of therapy when all the sputum cultures for M. tuberculosis were negative. A ratio of RD1 peptides ELISPOT counts over CD4+ T-cell counts greater than 0.21 yielded 100% sensitivity and 80% specificity for active TB. Conversely, response to RD1 intact proteins was not statistically different between subjects with or without TB at the time of recruitment; however a ratio of RD1 proteins ELISPOT counts over CD4+ T-cell counts greater than 0.22 yielded 89% sensitivity and 70% specificity for active TB. Conclusion In this pilot study the response to selected RD1 peptides is associated with TB disease in HIV-infected individuals in a high TB endemic country. This response decreases after successful therapy. The potential of the novel approach of relating ELISPOT spot-forming cell number and CD4+ T-cell count may improve the possibility of diagnosing active TB and deserves further evaluation.